A Qualitative Analysis of Generation Z's Motivation in Choosing Green Jobs and the Contribution of GHRM Practices in Sulawesi - Syahrul, Khaidir (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This qualitative study investigates the nuanced motivations driving Generation Z in Sulawesi towards green jobs and examines how Green Human Resource Management (GHRM) practices contribute to fostering this critical alignment. Faced with direct environmental challenges and a strong sense of purpose, Gen Z in Sulawesi increasingly seeks careers that offer tangible positive environmental and societal impact beyond financial remuneration. Employing a phenomenological approach, the research gathered in-depth insights through semi-structured interviews with Gen Z individuals engaged in or aspiring to green jobs, and HR practitioners involved in GHRM initiatives across Sulawesi. Findings reveal that Gen Z's motivation is deeply rooted in personal values aligning with ecological stewardship and a desire for meaningful contribution, enhancing their attitude towards green jobs as conceptualized by the Theory of Planned Behavior. Furthermore, the study demonstrates that authentic GHRM practices, including transparent green employer branding and supportive internal environmental initiatives, significantly enhance the attractiveness and perceived behavioral control of green jobs for this demographic. These insights underscore the imperative for organizations in Sulawesi to integrate genuine sustainability efforts into their core HR strategies to effectively attract, engage, and retain the vital green talent essential for the region's sustainable development.